Leading Through Language: Choose the words that influence and inspire - Egnal, Bart (Wiley, 2016)
The author shows leaders how to inspire when they communicate. He explains how to approach communication as an opportunity to lead, by first defending a clear, convincing message, and then by delivering that message using powerfull language....